Is Cognitive Behaviour Therapy Effective for Borderline Personality Disorder : A Case Report and Review of Literature - Autar Singh, Gurpreet Kaur; Midin, Marhani; Mohd Salleh Sahimi, Hajar; Sarip, Shalisah (IIUM Medical Journal Malaysia, 2023)
Managing people with borderline personality disorder (BPD) is an arduous task due to the complexity of the condition. This paper describes the role of Cognitive Behaviour Therapy (CBT) in a patient diagnosed with BPD who has undergone a modified DBT skill group training. Despite receiving multiple interventions in the past, this patient had her bouts of struggles living with this illness which required a new approach to facilitate her recovery. A trial of a short-term, 12 session-ed treatment of mindfulness-based CBT was commenced. In this case report we describe the challenges and modifications which surpass during this session and literature review on the role of CBT on BPD.